(untitled) (The Journal of Medicine, Humanity and Media, 2025)
Weibo serves as an important platform for the general public to obtain information about people with autism spectrum disorder. This study focused on 33 popular Weibo trends related to autism during the period of 2020-2022, and employed a combination of LDA topic modeling and sentiment analysis to explore the attitudes and foci of Weibo users towards individuals with autism. The findings showed that Weibo users focused on five major topics: social care for individuals with autism, medical knowledge dissemination, educational and rehabilitation, parents of children with autism, and autistic savants. In terms of sentiment analysis, Weibo users exhibited overwhelmingly positive attitudes towards individuals with autism, with very few instances of neutral or negative sentiments. The image of the autism population is mainly portrayed as positive and optimistic. The findings provide insights into understanding the mechanism of autism information dissemination on social media and practical implications to the online health communication of autism on Weibo platforms.